Prognostic significance of beta-2 adrenergic receptor in oral squamous cell carcinoma - Bravo-Calderon, Diego Mauricio; Oliveira, Denise Tostes; Marana, Aparecido Nilceu [UNESP]; Nonogaki, Suely; Carvalho, Andre Lopes; Kowalski, Luiz Paulo (IOS Press, 2011)
The aim of this study was to evaluate the expression of beta 2-adrenergic receptor (beta 2-AR) in oral squamous cell carcinoma (OSCC) and to investigate the correlations between expression level and clinical characteristics, outcome, and patient prognosis. A total of 106 OSCC patients underwent surgical treatment at the A. C. Camargo Cancer Hospital, São Paulo, Brazil, were analyzed for clinicopathological data, treatment, tumor outcome, prognosis and immunohistochemical expression of beta 2-AR. The beta 2-AR expression was statistically analyzed relative to clinicopathological variables and survival using the Chi-square test, Kaplan-Meier curves and Cox regression model. Most OSCC (72.6%) exhibited malignant cells with strong cytoplasmatic and membranous beta 2-AR expression. beta 2-AR expression was significantly associated with alcohol (p = 0.021), simultaneous consumption of alcohol and tobacco (p = 0.014) and T stage (p = 0.07). In addition, OSCC patients who exhibited strong beta 2-AR expression demonstrated a higher rate of overall survival (p = 0.001) and cancer specific survival (p = 0.004) compared to patients with weak/negative beta 2-AR expression. The Cox regression model demonstrated that strong beta 2-AR expression was an independent favorable prognostic factor for OSCC patients. These results suggest that the strong malignant cell beta 2-AR expression is a favorable prognostic factor for OSCC patients and could be used as a target for new anti-neoplastic pharmacological strategies.
Keywords: Oral cancer; adrenergic receptor; stress